Retrospective screening for SARS‐CoV‐2 among influenza‐like illness hospitalizations: 2018–2019 and 2019–2020 seasons, Valencia region, Spain. Issue 1 (16th September 2021) - Mira‐Iglesias, Ainara; Mengual‐Chuliá, Beatriz; Cano, Laura; García‐Rubio, Javier; Tortajada‐Girbés, Miguel; Carballido‐Fernández, Mario; Mollar‐Maseres, Juan; Schwarz‐Chavarri, Germán; García‐Esteban, Sandra; Puig‐Barberà, Joan; Díez‐Domingo, Javier; López‐Labrador, F. Xavier
Abstract: On 9 March 2020, the World Health Organization (WHO) Global Influenza Programme (GIP) asked participant sites on the Global Influenza Hospital Surveillance Network (GIHSN) to contribute to data collection concerning severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). We re‐analysed 5833 viral RNA archived samples collected prospectively from hospital admissions for influenza‐like illness (ILI) in the Valencia Region of Spain by the Valencia Hospital Surveillance Network for the Study of Influenza and Other Respiratory Viruses (VAHNSI) network (four hospitals, catchment area population 1 118 732) during the pre‐pandemic 2018/2019 ( n  = 4010) and pandemic 2019/2020 ( n  = 1823) influenza seasons for the presence of SARS‐CoV‐2. We did not find evidence for community‐acquired SARS‐CoV‐2 infection in hospital admissions for ILI in our region before early March 2020.